Chromosome numbers and their taxonomic implications for eight Brazilian andropogons (Poaceae: Andropogoneae) - Campbell, Christopher S.; Windisch, Paulo G. [UNESP] (Springer Nature, 1986)
Eleven chromosome counts are reported for Brazilian populations of eight species of Andropogon. Counts for five of the species are first reports for the species. Four of these species, A. arenarius, A. glaziovii, A. lateralis, and A. lindmanii, are hexaploids (n=30) and belong to a group of about a dozen species informally referred to as the Andropogon lateralis complex. Two other species of this complex, A. bicornis and A. hypogynus, we also found to be hexaploids, in agreement with previous reports. Diploid counts (n=10) for A. macrothrix (a first report) and A. virgatus (the same as two previous reports) support the morphological affinities of these two species to other species complexes within Andropogon. © 1986 the New York Botanical Garden.